Essential Facets of Competence That Enable Trust in Graduates: A Delphi Study Among Physician Educators in the Netherlands - Wijnen-Meijer, Marjo (The Accreditation Council for Graduate Medical Education, 2013)
BACKGROUND: There is a need for valid methods to assess the readiness for clinical practice of recently graduated physicians. To develop these methods, it is relevant to know the general features of trainees' performance that facilitate supervisors' trust in their ability to perform critical clinical tasks. OBJECTIVE: To discover such essential facets of competence (FOCs), based on the opinion of experienced physician educators. METHODS: We conducted a Delphi study, consisting of 2 rounds, among 18 experienced physician educators in the Netherlands. Mean, standard deviation, level of agreement, and skewness were calculated for the importance of FOCs for making entrustment decisions. The study yielded a list of 25 FOCs. RESULTS: In the first round, means were between 6.50 and 7.00 on a 7-point Likert scale (SD, 0.42–2.18); in the second round, means ranged from 5.45 to 6.90 (SD, 0.3–2.02). The level of agreement was high for 92% of the FOCs in the first round and 100% of the FOCs in the second round. CONCLUSIONS: Our Delphi study found consensus among experts about FOCs that are important for clinical entrustment decisions.